Assessment of urban product consumption and relevant waste management - Nuanchan Singkran (2020)
© 2020, Springer Japan KK, part of Springer Nature. The consumption inefficiency (CI) index of Bangkok of major product groups (food, plastic, paper, textile, and glass) was annually determined from 1994 to 2018. The CI index ranges from 0 to 1; the higher the index, the lower the consumption efficiency. The results showed that Bangkok had low consumption efficiency with mean CI indices of 0.8 for plastic, 0.7 for glass, and 0.5 for paper product groups. Bangkok had lower mean CI indices of 0.2 for textile and 0.4 for food products. These findings revealed that the high consumption of Bangkokians of plastic, glass, and paper products and inefficient waste sorting (for reuse and/or recycling) before disposal were the co-factors affecting the consumption efficiency of Bangkok. To increase the city’s consumption efficiency, minimization of product consumption and waste for disposal should be considered simultaneously with the improvement of relevant practices and regulations on waste minimization.